#JeSuisCharlie & #PeaceForParis: Appropriation, reformulation and circulation of Liberty Leading the People on socio-digital networks during the Paris attacks - Justine, Simon (Scripta, 2018)
The proposed discourse analysis concerns multimodal tweets which posted the painting Liberty Leading the People of Eugène Delacroix during the Paris attacks of 2015. In 2015, France was subjected to two tragic terrorist attacks on January 7th, 8th and 9th - with the most famous attack against the satiric newspaper Charlie Hebdo and the hostages being taken in a kosher supermarket - and a series of shootings and murderous suicide attacks on November 13th in Paris and Saint-Denis. In reaction to these attacks, several events to support the victims were organized. Several gatherings - called “republican marches” - took place in tribute to the victims on 10th and 11th January. However, following the November 13th events, demonstrations on the public highway were forbidden when a state of emergency was declared by President François Hollande the day after.